Self compacting concrete incorporating slag - Pek, Qia Quan. (2011)
As the world shift its focus towards green technology and being environmentally friendly, concrete, being the most used construction material, have areas for improvement. Cement being the major contributor to greenhouse gases during concrete production and energy used to vibrate and compact the fresh concrete are 2 areas for improvement. Thus the answer to the concern above is the use of mineral admixture; slag in this case, as replacement in self compacting concrete. The project will be looking at fresh and hardened concrete properties to determine the suitability of slag as replacement for cement in self compacting concrete. Fresh concrete properties include flowability and hardened properties include compressive strength and durability such as chloride penetration and elastic modulus. The study has shown that slag replacement is beneficial for hardened properties of SCC and has limited effect on the fresh properties. Subsequently, efficiency of slag was taken into consideration in bid to reduce cement content while attempting to keep its properties satisfactory, however, its fresh concrete properties were not desirable though the compressive strength was satisfactory.